A survey on bloat in southern Australian beef production systems. Issue 3 (21st December 2022) - Allworth, MB; McQuillan, M; McGrath, SR; Wilson, CS; Hernandez‐Jover, M
Abstract : Frothy bloat, associated predominantly with grazing legume‐based pastures, is considered the second most costly disease in beef cattle in southern Australia, costing $84.4 M annually. It frequently results in the sudden death of cattle. In response to concerns from cattle producers, an online survey was conducted in southern Australia in late 2020 to determine the impact of bloat, identify risk factors and determine the efficacy of current preventive measures. For 217 responses, over two‐thirds (70%) of producers reported bloat occurring in the previous 12 months, with estimated morbidity and mortality rates of 3.7% and 5.0% respectively. Bloat was associated with clover or clover‐dominant paddocks (79%) and was not associated with grass or grass‐dominant pastures or low clover pastures (92%) nor grazing crops (27%). For bloat that occurred in the past 12 months, cattle were very commonly grazing on clover or clover‐dominant paddocks (90%) and occasionally lucerne‐dominated paddocks (7%). Two‐thirds of producers reported having preventive measures in place when losses occurred. Bayesian Network analysis confirmed that grazing clover‐based pastures for more than 7 days, yearling cattle and the months of July–September were the main risk factors for bloat occurrence, with pasture type (clover) being the most important. Conversely, no clear relationship between weather conditions and bloat occurrence was evident. This survey highlights the known risk of clover‐based pastures for causing bloat in cattle, and that losses occur in many cases despite preventive measures being used. This suggests that current methods for preventing bloat in cattle are suboptimal.